Penyuluhan Osteoathritis Lutut untuk Meningkatkan Pengetahuan Komunitas Lansia di Desa Watugede Kecamatan Singosari - Nadifa Athifatun Aqiila; Rakhmad Rosadi; Ratna Vidya Amelia (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2024)
The elderly range of diseases, one of which is reduced fluid in the knee joint will result in knee osteoarthritis. Osteoarthritis is a degenerative disease that attacks the articular cartilage in the knee and causes changes in the joint along with the subchondral bone, which is characterized by knee pain, pain, and stiffness in the morning, pain when going up and down stairs, and feeling pain when squatting for a long time. This counseling aims to increase knowledge and insight for the elderly regarding knee osteoarthritis, one of the most common health problems. The method in this study uses counseling methods with leaflet media. The results obtained in the elderly integrated health service post understand the provision of counseling related to knee osteoarthritis.